IMPLEMENTASI NILAI CLEAR – K DALAM MENINGKATKAN MUTU PELAYANAN PUBLIK DI KPPN SIDOARJO - Kurnianto, Daniel Arvin; Sari , Sarah Meirina (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
This study examines the implementation of the CLEAR–K values (Fast, Clear, Efficient, Trustworthy, Friendly, Perfection) in improving the quality of public services at the State Treasury Service Office (KPPN) Sidoarjo. Using a descriptive qualitative approach, data were obtained through interviews, observations, and documentation to understand how each value is applied in daily service practices. The findings show that the CLEAR–K values have been reflected in the work culture of KPPN Sidoarjo, although several challenges remain, including uneven digital literacy among work units, system disruptions, and the dynamic nature of regulatory changes. The implementation was analyzed using Edward III’s policy implementation model, emphasizing communication, resources, disposition, and bureaucratic structure. The study concludes that the application of CLEAR–K contributes positively to service quality, yet requires continuous refinement to ensure consistent and optimal performance.